Trematoda Darah: Schistosomiasis pada Sistem Saraf Pusat - Yuliana, Yuliana; Machrumnizar, Machrumnizar (Fakultas Kedokteran Universitas Trisakti, 2025)
Schistosomiasis (bilharzia) is a disease caused by blood trematode worms of the genus Schistosoma, which can be acute or chronic. There are five species of Schistosoma (S. japonicum, S. mansoni, S. intercalatum, S. Mekongi, and S. haematobium) known to infect humans, which are distributed across a wide geographic range. Severe clinical symptoms of schistosomiasis infection on the central nervous system (CNS) are caused by the deposition of eggs when adult worms migrate abnormally to the brain or spinal cord. As a result, radiculopathy, myelopathy, increased intracranial pressure, and clinical sequelae occur. Each species shows different tendencies for atopic infections and clinical symptoms. The most common neurological symptom associated with Schistosoma mansoni or S. haematobium infections is myelopathy, while severe encephalitis is more likely to be caused by S. japonicum infections. The symptoms of encephalopathy can manifest as headache, vision disturbances, delirium, convulsions, motor limitations, and ataxia. Spinal abnormalities may lead to backache, lower limb radiating discomfort, muscular weakness, loss of sensation, and urinary impairment. Histopathological analysis, which shows granulomas and Schistosoma eggs, is necessary for a definitive diagnosis. Current management involves surgical procedures, steroids, and schistosomicide drugs. Corticosteroids are administered in the acute stage, and praziquantel is given after the female worm begins to lay eggs. If medical intervention fails to relieve compression or medullary degeneration, surgery should be postponed in some instances. The earlier a diagnosis is identified and proper therapy begins, the better the patient's outcome.